Perkembangan Kehidupan Masyarakat Desa Lubuk Seberuk Kecamatan Lempuing Jaya Kabupaten Ogan Komering Ilir Dalam Bidang Pendidikan Tahun 1983-2013 - Ali, Bintang Hidir; Supriyanto, Supriyanto; Asmi, Adhitya Rol (Journal of Indonesian History, 2019)
This study entitled "Development of Community Life in Lubuk Seberuk Village, Lempuing Jaya District, Ogan Komering Ilir Regency in the Field of Education in 1983-2013". The problem of this study is how the development of Social life in Lubuk Seberuk Village, Lempuing Jaya District, Ogan Komering Ilir Regency in 1983- 2013 and how the development of Education in Lubuk Seberuk Village, Lempuing Jaya District, Ogan Komering Ilir Regency in 1983-2013. The purpose of this study is to explain the development of Social life in Lubuk Seberuk Village, Lempuing Jaya District, Ogan Komering Ilir Regency in 1983-2013 and explain the Development of Education in Lubuk Seberuk Village from 1983-2013. This research is a type of historical research, a systematic framework for collecting historical sources, with criticism of the sources conducted by researchers, and assessments in selecting facts to obtain the truth and review the sources in a written form. The aspects observed in this study are economic aspects, social aspects, and educational aspects which include the development of Social life in Lubuk Seberuk Village and the advancement of education in Lubuk Seberuk Village. Keywords: Development, Social Life, Social, Economy, Education.